Comparing self-reports to national register data in the detection of disabling mental and musculoskeletal disorders among ageing women. (October 2022) - Heikkinen, Jeremi; Honkanen, Risto J.; Williams, Lana J.; Quirk, Shae; Kröger, Heikki; Koivumaa-Honkanen, Heli
Highlights: Self-reports grossly underestimate the prevalence of disabling mental disorders and markedly that of musculoskeletal disorders among ageing women. Older age is related to non-reporting of both mental and musculoskeletal disorders. Additional sources of information to self-reports are needed for the detection of disabling mental and musculoskeletal disorders prior to older age. Abstract: Background: Self-reports of diseases are used in research due to time and cost efficiency. Mental disorders (MDs) and musculoskeletal disorders (MSDs) are the leading causes of global disability. Aims: To investigate how self-reports detect physician-diagnosed severe MDs and MSDs in postmenopausal women. Methods: In the population-based OSTPRE cohort, 1466 women (aged 57–66) had received a permanent work disability pension (DP) due to 'MDs only' (n = 336), 'MSDs only' (n = 926) or 'MDs + MSDs' (n = 204) by the end of 1998 and responded to a postal enquiry in 1999. In 2009, 1029 women responded to a follow-up enquiry. Self-reports were cross-checked against register data on DPs. Results: In 1999, 47 % of the participants in the 'MDs only' and 21 % in the 'MDs + MSDs' reported DPs due to MDs, whereas 75 % in the 'MSDs only' and 67 % in the 'MDs + MSDs' reported DPs due to MSDs. By 2009, this discrepancy increased, with the respective figures being 34 % and 19 % for MDs and 75 % for both MSDs groups. In 1999, older age was related to non-reporting in the three groups (each: p ≤ 0.001). Conclusion: Self-reports grossly underestimate the prevalence of disabling MDs and considerably that of MSDs among ageing women. Thus, additional sources of information are needed.